Steroid treatment response to post SARS-CoV-2 PANS symptoms: Case series - Berloffa, Stefano; Salvati, Andrea; Pantalone, Gloria; Falcioni, Ludovica; Rizzi, Micaela M.; Naldini, Francesca; Masi, Gabriele; Gagliano, Antonella (Frontiers in Neurology, 2023)
Pediatric Acute-onset Neuropsychiatric Syndrome (PANS) is characterized by a wide spectrum of symptoms, including onset obsessive-compulsive disorder and/or severely restricted food intake, associated with emotional symptoms, behavioral symptoms, developmental regression, somatic symptoms. Among the possible triggering agents, infectious agents have been extensively explored. Recently, sporadic case reports describe a possible association between PANS and Sars-Cov-2 infection, but data on clinical presentation and treatment are still scarce. We describe 10 children with acute onset or relapse of PANS symptoms after Sars-Cov-2 infection. Standardized measures (CBCL-CPRS-C-GAS/CGI-S-Y-BOCS-PANSS,-YGTSS) were used to describe clinical picture. Efficacy of a pulse treatment with steroids for 3 consecutive months was assessed. Our data suggests that clinical presentation of COVID triggered PANS is largely overlapping to that reported in typical PANS, including acute onset, with OCD and/or eating disorders, and associated symptoms. Our data suggest that a treatment with corticosteroids may be beneficial on both global clinical severity and global functioning. No serious adverse effects were observed. Both OCD symptoms and tics consistently improved. Among psychiatric symptoms, affective and oppositional symptoms, appeared more sensitive to the steroid treatment then the other symptoms. Conclusion: Our study confirms that COVID infection in children and adolescents could trigger acute-onset neuropsychiatric symptoms. Thus, in children and adolescents with COVID, a specific neuropsychiatric follow-up should be routinely included. Even if small sample size and a follow-up with only baseline and endpoint (after eight weeks) limits the conclusions, it seems that steroid treatment in acute phase may be beneficial and well tolerated.